Isolated hoarseness revealing an occult extensive aortic dissection — A rare case of Ortner Syndrome - Sonam Jamtsho; Sangay Dorji (Bhutan Health Journal, 2026)
Hoarseness of voice due to vocal cord palsy may indicate an underlying sinister pathology. However, vocal cord paralysis as the sole manifestation of aortic dissection and aneurysm is rare. We report the case of a 63-year-old man with diabetes mellitus, hypertension and a 40-year smoking history, who presented with hoarseness to the ENT Outpatient Department of Jigme Dorji Wangchuck National Referral Hospital. Evaluation revealed left vocal cord palsy, and a chest X-ray showing mediastinal widening prompted further imaging. Contrast-enhanced computed tomography revealed extensive aortic dissection. A multidisciplinary discussion involving cardiology, cardiothoracic surgery, ENT and the patient’s family led to a decision of conservative management with strict blood pressure control and smoking cessation.